Od "funkcjonalnej" do "procesowej" obsługi klienta - na przykładzie firmy Amato - Tracz, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
It can be observed nowadays that the firms have tendency to reengineer their structures from a main processes viewpoint. Building a process oriented company is not a simple matter - it is related to deep changes and fundamental conversion of organization; requires time, vision, involvement and consequence in its implementation. The article presents the case of a company that has undertaken to change the orientation of its key process: from "functional" to "process oriented". The customer service was that core process. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 286-293